A variação na concordância nominal de número no falar do Cariri cearense - Tabosa, Maria Vanderlúcia Sousa (2016)
This work analyzes the nominal agreement of number between the constituents of the nominal phrase (NP) in Portuguese spoken in region of Cariri, in the state of Ceará, Brazil, in light of the theoretical-methodological assumptions of the Theory of Variation and Linguistic Change (LABOV, WEINREICH, HERZOG, 2006; LABOV 1978, 1994, 2001). Its general objective is to investigate to what extent the linguistic factors position of the elements in the phrase, class and position in relation to nucleus and nuclear position; grammatical class of the nominal phrase and morpho-phonological processes of formation of plural; tonicity of the syllables of the singular lexical items and precedent marks of plural within the scope of the nominal phrase, and extralinguistic factors sex; years of schooling and age range condition the use of nominal agreement in the speech of the towns that make up the CRAJUBAR region – Crato, Juazeiro do Norte, and Barbalha – in the region of Cariri, in the south of Ceará, Brazil. For quantitative analysis, it was collected 3304 data from interviews with 24 informants in these three towns. The interviews are present in the corpus PROFALA (The Portuguese spoken in Ceará). The data were submitted to statistical analysis in the GoldVarb X program. For the nine groups of factors initially considered, six groups were selected as significant: position of the elements in the nominal phrase, class and position in relation to the nucleus and nuclear position; morpho-phonological processes of plural formation; precedent marks of plural in the scope of the nominal phrase and the extralinguistic factors; sex; and age group. Regarding the results obtained, it was identified a high marking index totaling a percentage of 76.9%. Women had a marking probability higher than men, and informants between the ages of 15 and 25 years and 50 years old presented rates higher than the informants with ages ranging from 26 to 49 years.